2018
DOI: 10.1007/s00115-018-0545-x
|View full text |Cite
|
Sign up to set email alerts
|

Prävalenz schlafbezogener Atmungsstörungen bei stationären Patienten mit psychischen Erkrankungen

Abstract: The high prevalence indicates that sleep apnea is a common sleep disorder among psychiatric patients. Although OSAS can lead to substantial disorders of the mental state and when untreated is accompanied by serious somatic health problems, screening procedures are not part of the routine work-up in psychiatric hospitals; therefore, sleep apnea is presumably underdiagnosed in psychiatric patients. In view of the results of this and previous studies, this topic complex should be the subject of further research s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…For PTSD/anxiety disorders, shared neurobiological and/or genetic factors and overlapping characteristics such as hyperarousal have been implied as well (Freeman et al, 2020). In our study, the prevalence of suspected SBD was moderate compared to previously reported prevalence rates in a clinical mental health sample (Behr et al, 2018). We did observe a relatively high prevalence of suspected SBD in participants with SUD and those with ADHD.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…For PTSD/anxiety disorders, shared neurobiological and/or genetic factors and overlapping characteristics such as hyperarousal have been implied as well (Freeman et al, 2020). In our study, the prevalence of suspected SBD was moderate compared to previously reported prevalence rates in a clinical mental health sample (Behr et al, 2018). We did observe a relatively high prevalence of suspected SBD in participants with SUD and those with ADHD.…”
Section: Discussioncontrasting
confidence: 69%
“…Particularly the prevalence estimates of sleep disorders that require extensive physiological diagnostic procedures, such as SBD, may not be sufficiently accurate. For instance, a study in a clinical mental health population utilising polysomnography‐based diagnosis of SBD found the substantially higher prevalence of 23.7% (Behr et al, 2018), which may, among others, suggest that our suspected prevalence might be an underestimation. In contrast to SBD, the clinical diagnosis of the SRMD RLS is based on self‐reported symptoms.…”
Section: Discussionmentioning
confidence: 88%
“…It remains unclear whether these patients had an additional specific sleep disorder, such as sleep apnea, so substantial conclusions cannot be drawn. A previous multicenter study on a comparable clinical sample found a high prevalence (21.7%) of previously unknown obstructive sleep apnea syndrome (OSAS) in 298 psychiatric inpatients ( 86 ). An increased comorbidity of RLS in patients with OSAS has also been demonstrated, especially in patients with insomnia symptoms ( 87 , 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice and in many studies, the degree of objective sleep disturbance in these people is entirely neglected, because PSG and PG studies are just not performed. Given an up to 25% prevalence of, e.g., sleep apnoea syndrome in psychiatric patients [30] and, vice versa, a prevalence of insomnia complaints in about 50% of those affected by sleep apnoea [31], this is of obvious concern.…”
Section: The Case Of Insomnia Disordermentioning
confidence: 99%
“…One important reason is that insomnia complaints are the consequence of a variety of distinct psychiatric and somatic disorders which are not stringently excluded when diagnosing insomnia disorder. No doubt, for example, insomnia complaints in a patient with obstructive sleep apnoea, or depression, or even both [30], have a different aetiological and pathophysiological background than in patients without these conditions. The second reason is that insomnia is seen as a sleep disorder, but biological sleep is not consequently taken into account.…”
Section: Negative Physical Consequences Of Insomnia Disorder Are Prob...mentioning
confidence: 99%